Bismuth oxide nanoflakes for passive Q-switching in a C-band erbium doped fiber laser - Ahmad, Harith; Aidit, Siti Nabila; Yusoff, Norazriena (Elsevier, 2018)
In this work, bismuth oxide (Bi2O3) nanoflakes suspended in a polyvinyl alcohol (PVA) host are used as a saturable absorber (SA) in an erbium-doped fiber laser (EDFL). The facile hydrothermal method is employed to synthesize the Bi2O3 nanoflakes as the SA, which provides stable Q-switching at a central wavelength of 1564 nm with a maximum pulse energy of 21.31 nJ. The generated pulses have repetition rates of 28.41–49.51 kHz and pulse widths of 4.9–1.55 µs over the available pump power range. The Bi2O3-PVA based SA also has a high signal-to-noise ratio (SNR) of 51.28 dB, indicating a significantly stable output and demonstrating the high potential of the fabricated Bi2O3-PVA film for practical applications. To the best of the author's knowledge, this is the first report of the use of a Bi2O3-PVA based SA for Q-switching in a C-band EDFL region.